2015
DOI: 10.1111/ane.12345
|View full text |Cite
|
Sign up to set email alerts
|

Alteration profile of executive functions in multiple sclerosis

Abstract: Cognitive flexibility, inhibition and abstraction ability were the three components of EF most deficient. The patients with the worst performance were those with progressive forms and a high EDSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 31 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…Furthermore, our results confirm the primary engagement of verbal memory and executive functions in very mild levels of clinical disability in accordance with previous studies [7, 29, 30]. Cerezo García and colleagues [29], in a small cohort of patients, found that 24% of very mild RRMS patients had memory deficits and 80% showed information processing speed and executive function impairment, especially in the maintenance of nonautomatic strategies and conceptual/categorization tasks, usually attributed to prefrontal regions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, our results confirm the primary engagement of verbal memory and executive functions in very mild levels of clinical disability in accordance with previous studies [7, 29, 30]. Cerezo García and colleagues [29], in a small cohort of patients, found that 24% of very mild RRMS patients had memory deficits and 80% showed information processing speed and executive function impairment, especially in the maintenance of nonautomatic strategies and conceptual/categorization tasks, usually attributed to prefrontal regions.…”
Section: Discussionsupporting
confidence: 93%
“…Cerezo García and colleagues [29], in a small cohort of patients, found that 24% of very mild RRMS patients had memory deficits and 80% showed information processing speed and executive function impairment, especially in the maintenance of nonautomatic strategies and conceptual/categorization tasks, usually attributed to prefrontal regions. Roca and colleagues [30] showed that MS patients with low physical disability presented a fronto-subcortical pattern with impairment in memory, decision-making, working memory, and planning, as well as in goal-oriented behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can occur at any point during the disease’s progression, and it most often affects memory, attention, and processing speed (Shatil, Metzer, Horvitz, & Miller, 2010). Persons with MS have also been found to perform poorly on executive function tests (Arnett, et al, 1997; Drew, Tippett, Starkey, & Isler, 2008; Garcia, Plasencia, & Benito, 2015) Halper, et al also proposed that the ability to grasp complex concepts, plan, and adhere to a schedule can be affected (Halper, et al, 2003). Such impairments can seriously impact daily functioning, including one’s employment (Rao et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Information processing in particular is the cognitive domain most widely affected by MS and is notably the first deficit to emerge [1719]. MS patients with progressive disease course, especially secondary progressive, can also experience a range of cognitive deficits and associated disability [20]. MS has been associated with delayed recall performance and lower acquisition of verbal memory [21] and episodic short-term memory [22].…”
Section: Introductionmentioning
confidence: 99%